Transfer Behaviour in Migrant Sending Communities - Susan Steiner; Tanika Chakraborty; Bakhrom Mirkasimov (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Private transfers between households in developing countries have been extensively studied and shown to be economically important as mechanisms of risk sharing and income redistribution. We argue that migration and remittances have the potential to modify the prevalent transfer behaviour in migrant-sending communities. A priori, it is indeterminate whether migration and remittances strengthen or weaken the degree of private transfers. We use data from a detailed household survey in Kyrgyzstan, designed by the authors, to empirically study the effect of migration and remittances on both monetary and non-monetary transfers. We find that migrant households provide more monetary transfers and receive more non-monetary transfers compared with non-migrant households, particularly in rural areas. Furthermore, we find that the transfer of non-monetary help, in the form of labour, takes place only in the presence of labour constraints within the household. We argue that distinguishing between the nature of transfers, monetary or non-monetary, is important in the context of the vast literature investigating private transfer motives.
Keywords: F22; O12; I30; 330